1984
DOI: 10.1016/s0022-5347(17)50065-8
|View full text |Cite
|
Sign up to set email alerts
|

Rice Bran Treatment for Patients with Hypercalciuric Stones: Experimental and Clinical Studies

Abstract: The purpose of this study is to confirm the hypocalciuric effect of rice bran experimentally and clinically. Urinary calcium excretion and its absorption in the intestine were reduced significantly by rice bran or phytin in rats fed high calcium diets, while there were no significant decreases with a low calcium diet. For the clinical study 70 patients with idiopathic hypercalciuria were treated with rice bran (10 gm. twice daily) for 1 month to 3 years. In almost all patients rice bran caused a significant de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(33 citation statements)
references
References 18 publications
1
31
0
1
Order By: Relevance
“…Reduced phytate intake may be among the causes for the increased incidence of renal stones in industrialized countries (203). Henneman et al (206) used pure Na-phytate, and Ohkawa et al (207) used a diet containing high phytate concentration for the treatment of hypercalciuria and kidney stones. Since, in addition to above mentioned effects of phytic acid, it has been presented that IP6 may be useful in the management of HIV infection and associated immunodeficiency-related problems (111), the health effects presently associated with phytic acid appear to be as complex and numerous as those associated with dietary fibre.…”
Section: Anticancer Functions Of Myoinositol Phosphatesmentioning
confidence: 99%
“…Reduced phytate intake may be among the causes for the increased incidence of renal stones in industrialized countries (203). Henneman et al (206) used pure Na-phytate, and Ohkawa et al (207) used a diet containing high phytate concentration for the treatment of hypercalciuria and kidney stones. Since, in addition to above mentioned effects of phytic acid, it has been presented that IP6 may be useful in the management of HIV infection and associated immunodeficiency-related problems (111), the health effects presently associated with phytic acid appear to be as complex and numerous as those associated with dietary fibre.…”
Section: Anticancer Functions Of Myoinositol Phosphatesmentioning
confidence: 99%
“…The inhibitory effect of phytic acid on the amount of calcium excreted with urine was also found in experiments on rats fed a diet rich in this element (Ohkawa et al, 1984).…”
mentioning
confidence: 67%
“…However, there are other factors to consider such as bioavailability of the dietary oxalate, and nutritional factors such as dietary fibre and phytate. Some studies have shown that dietary phytic acid (James et al, 1978;Jahnen et al, 1992) could reduce the intestinal absorption of calcium by binding calcium in the gastrointestinal tract (Ohkawa et al, 1983(Ohkawa et al, , 1984Gleeson et al, 1990;Ebisuno et al, 1991). Consequently, more free oxalate could be available to be absorbed.…”
Section: Discussionmentioning
confidence: 99%